Students’ Self Revision in Essay Writing - Mohammad Febryanto (Jurnal Bahasa Inggris Terapan, 2017)
This study investigates self-revision in essay writing conducted by 6 students. The analysis is based ondetermining common revised errors. The data have been reduced based on Language Related Episodes (LREs). The result shows that there are revision consisting of 1 change in punctuation both in first and second essay, 5 changes spelling in first essay, 19 changes vocabulary in the first essay and 6 changes in second essay, 25 changes in word form correction in the first essay and 27 changes in the second essay, and there are 19 changes in sentence level the first essay and 13 changes in the second one. This indicates that the self-revision is predominantly focused onthe word level changes particularly in morphology. Keywords: self-revision, common revised errors, Language Related Episodes (LREs)